An Open-Source Spanish Video Game as a Case Study for the Development of an Interface for Users with Visual Impairment - Güimil, Estefanía (2017)
With the growth of information provided through computer systems, it is fundamental and legally necessary, that everyone have equal access to the information in order to live fairly. For the last few years there have been a positive trend in the software industry to include people with disabilities as their target users. As a consequence of this, access for visually impaired users to software is improving. This brings new challenges from the Human Computer Interaction viewpoint. This paper describes the design, development and evaluation of an open source video game for visually impaired users in Spanish. This game was conceived as a case study for the Human Computer Interaction theory applied to those with visual problems.